Kabata Banda & the significance of Islamic eco-theology education - Farid, Muhammad; Latuapo, Abdullah (Jurnal Cakrawala Pendidikan, 2024)
The environmental crisis is a real threat to human survival. Climate change, natural disasters, and food crises are some of the devastating impacts that can have a major impact on the human population. The Banda Islands have a wide water zone with diverse marine biota but face the threat of natural disasters from active volcanoes and human behaviour that is not environmentally friendly. Historically, Banda has a tradition that is very close to coastal nature. This is revealed in their traditional song known as Kabata Belang, often sung while rowing a traditional boat (Belang) in various community cultural stages. By adopting phenomenology perspectives, this research is focused on reviewing the narration of the Fiat' Kabata belang sacrament songs to seek out the implied values of environmental ethics and its urgency in handling coastal environmental problems in Banda Naira today. The results show that Kabata Belang contains both theological and ecological values (eco-theology) apart from being an instrument of traditional rituals. There are 13 stanzas in Fiat village Kabata Belang that are oriented towards maintaining several coastal natural objects, such as mountains, coasts, birds, and fish. The singing of the Kabata Belang as a traditional wisdom functions as an "advisor" for the people of Banda today to preserve the marine and coastal environment. This research recommends the importance of writing down the Kabata text, complete with pictures and articulations that are more accessible to the public as a guidebook, especially for the younger generation to understand better and participate in creative efforts to preserve the coastal and marine environment in their everyday lives.